The Effect of Islamic Financial Literacy on the Decision to Use Islamic Banking Services in the City of Ternate with Religion as a Moderating Variable - Muhammad Muhammad; Abdul Hadi Sirat; E. Hartaty Hadady (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to examine the influence of islamic financial literacy towards the utilization of islamic banking services. Religiosity as a moderating variable. The sample in this study were customer of Islamic banking in Ternate City taken by purposive sampling method. The number of samples used were 100 respondents. The method of analysis of this research used simple linear regression analysis and moderated regression analysis with SPSS. The result of this research showed that Islamic financial literacy has a positive and significant effect to the utilization of islamic banking services. Meanwhile religiosity weakens the connection between islamic financial literacy and the utilization of islamic banking services.